2020
DOI: 10.7554/elife.56945
|View full text |Cite
|
Sign up to set email alerts
|

Doa10 is a membrane protein retrotranslocase in ER-associated protein degradation

Abstract: In endoplasmic reticulum-associated protein degradation (ERAD), membrane proteins are ubiquitinated, extracted from the membrane, and degraded by the proteasome. The cytosolic ATPase Cdc48 drives extraction by pulling on polyubiquitinated substrates. How hydrophobic transmembrane (TM) segments are moved from the phospholipid bilayer into cytosol, often together with hydrophilic and folded ER luminal protein parts, is not known. Using a reconstituted system with purified proteins from Saccharomyces cerevisiae, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 100 publications
1
39
0
Order By: Relevance
“…Precedent for the latter is found in the sterolinduced degradation of Hmg2p and its mammalian equivalent HMGCR (another rate-limiting enzyme of cholesterol synthesis), which also involves direct interaction with the proteasome at the ER membrane [42,43]. In the case of SM, the AAA+ ATPase VCP likely provides the driving force to extract the membraneassociated components of the SM-N100 domain for degradation, although MARCHF6 may also contribute given the retrotranslocase function of Doa10p [44]. The role of deubiquitinases in SM truncation is less clear, but may involve the removal of ubiquitin chains from the Lys-82/90/100 cluster to enable processing by VCP or entry into the proteasome [45,46].…”
Section: Proteasomal Truncation Of Smmentioning
confidence: 99%
“…Precedent for the latter is found in the sterolinduced degradation of Hmg2p and its mammalian equivalent HMGCR (another rate-limiting enzyme of cholesterol synthesis), which also involves direct interaction with the proteasome at the ER membrane [42,43]. In the case of SM, the AAA+ ATPase VCP likely provides the driving force to extract the membraneassociated components of the SM-N100 domain for degradation, although MARCHF6 may also contribute given the retrotranslocase function of Doa10p [44]. The role of deubiquitinases in SM truncation is less clear, but may involve the removal of ubiquitin chains from the Lys-82/90/100 cluster to enable processing by VCP or entry into the proteasome [45,46].…”
Section: Proteasomal Truncation Of Smmentioning
confidence: 99%
“…These data strongly suggested that, like the Asi complex, Doa10 promoted INMAD independently of Dfm1. Notably, recent in vitro studies suggest the possibility that purified Doa10 itself could serve as a retrotranslocon ( Schmidt et al , 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…More generally, this study and others suggest that a growing number of proteins possess the ability to retrotranslocate quality-control substrates out of or through lipid bilayers. These include, but as we show are not limited to, Hrd1, Dfm1, Doa10, and the Asi complex ( Baldridge and Rapoport, 2016 ; Schoebel et al ., 2017 ; Neal et al , 2018 , 2020; Natarajan et al , 2020 ; Schmidt et al , 2020 ; Vasic et al , 2020 ; Wu et al , 2020 ). While redundancy is a common feature of protein-quality-control pathways, it will be interesting to further dissect the biochemical and cell-biological nuances that necessitate these dedicated channels.…”
Section: Discussionmentioning
confidence: 99%
“…Substrates with abnormal structural domains in multiple regions may be degraded depending on both the Hrd1 and Doa10 complexes [ 45 , 46 ]. Substrates of the Doa10 complex include single- or multi-spanning membrane proteins in the ER and the inner nuclear membrane, as well as soluble proteins in the cytosol and nucleoplasm [ 19 , 44 , 47 , 48 , 49 , 50 , 51 , 52 ]. Unlike the Hrd1 complex, which comprises multiple components, the Doa10 complex is relatively simple and contains three ubiquitination enzymes: Ubc6, Ubc7, and Cue1.…”
Section: Er-associated Degradation In Yeastmentioning
confidence: 99%
“…The mechanism underlying the retro-translocation of membrane substrates, including Doa10 substrates, is ill-defined. The extraction of Ubc6, which is degraded in a Doa10-dependent manner [ 50 , 58 ], was recently reconstituted in vitro [ 52 ]. The results of this experiment suggest that the luminal domain is unfolded by the action of Cdc48/p97 in the cytosol and crosses the membrane in an unfolded state.…”
Section: Er-associated Degradation In Yeastmentioning
confidence: 99%